Peripheral Arterial Disease Detection Efforts with Ankle Brachial Index (ABI) Examination - Mulyanti Roberto Muliantino; Yuanita Ananda; Rika Sarfika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Peripheral Arterial Disease (PAD) is the third leading cause of atheroskeric vascular morbidity in coronary heart disease. The ankle-brachial index (ABI) is one way to assess peripheral arteries. This activity aims to identify people who are at risk or suffer from PAD. The method used is a medical examination, which includes ABI values, blood pressure, cholesterol levels, blood sugar, and uric acid. This medical examination was conducted on 41 people in RT 02 RW 06 Pasar Ambacang, Padang City. The screening results found that 17.07% of respondents had ABI values higher than 1.3 (severely calcified vessel), and 14.62% had ABI values in the range of 0.71-0.9 (mild obstruction). This activity also found respondents with first-stage hypertension (29.26%), second-stage hypertension (2.44%), high cholesterol levels (56.09%), high blood sugar levels (7.31%), and uric acid levels exceeding normal limits (7.31%). Screening efforts can be a preventive measure.